THE EFFECTIVENESS OF MACROS-BASED COGNITIVE DOMAIN EVALUATION MODEL IN SENIOR HIGH SCHOOL BASED ON THE CURRICULUM 2013 - Djoko Purnomo; Harjito Harjito; Rina Dwi Setyawati; Muhammad Prayito (Jurnal Infinity, 2016)
The particular objective of this study was to investigate the effectiveness of implementation of learning device in the form of macros-based cognitive domain evaluation model via E-learning applied at 10th grade of senior high school in the odd semester based on the curriculum 2013. The method of this study followed the procedures of R & D (Research & Development) developed by Borg and Gall. The results of the research and application development of macros-based evaluation model are effective which can be seen from (1) the results of students’ mastery learning, (2) students’ independence gives positive effect on learning outcomes, (3) the learning results of students who used macros-based learning evaluation model of cognitive domain are better rather than those in control class. Based on the above results, it can be concluded that macros-based learning evaluation model of cognitive domain tested has met the quality standards.